2013
DOI: 10.5152/tpd.2013.44
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic Nematodes of Fish in the Coastal Waters of Gökçeada

Abstract: Anisakis simplex and Contracaecum fabri, found in different 11 fish species, were the dominant species for this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
0
12
1
Order By: Relevance
“…In addition, one was identified as H. aduncum and the other Phylogenetic tree clearly indicated that all observed Hysterothylacium isolates clustered together with same species in monophyletic groups supporting of high bootstrap values over 92% (Fig. 1) [4][5][6][7]9,10,[28][29][30][31] . [6] and Zeus faber [8] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, one was identified as H. aduncum and the other Phylogenetic tree clearly indicated that all observed Hysterothylacium isolates clustered together with same species in monophyletic groups supporting of high bootstrap values over 92% (Fig. 1) [4][5][6][7]9,10,[28][29][30][31] . [6] and Zeus faber [8] .…”
Section: Resultsmentioning
confidence: 99%
“…It is gregarious, and it is found on the shelf or coastal pelagic on different bottoms at a depth range 0-350 m. B. boops is omnivorous, feeding mainly on benthic copepods and plants but is also planktonophagous (www.fishbase.org, version 06/2017). Hysterothylacium species have been already reported in B. boops from different regions of the world [6,11,12] .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Anisakis pegreffii is the most frequently isolated in many fish species from Mediterranean waters and appears to be responsible for many cases of human anisakiasis (9). In Turkey, A. simplex and A. pegreffii were morphologically identified different fish species (1,16); while A. pegreffii was molecularly detected in Trachurus trachurus (17). Moreover, A. simplex was morphologically found in Z. faber from the coastal waters of Gökçeada (1).Nematodes of genus Anisakis parasitize a wide range of marine hosts with marine mammals, especially cetaceans, serving as definitive hosts, while fish, squid and other invertebrates serve as paratenic or intermediate hosts.…”
Section: Akdeniz'de Yakalanan Dülger Balığındakimentioning
confidence: 99%
“…In Turkey, A. simplex and A. pegreffii were morphologically identified different fish species (1,16); while A. pegreffii was molecularly detected in Trachurus trachurus (17). Moreover, A. simplex was morphologically found in Z. faber from the coastal waters of Gökçeada (1).Nematodes of genus Anisakis parasitize a wide range of marine hosts with marine mammals, especially cetaceans, serving as definitive hosts, while fish, squid and other invertebrates serve as paratenic or intermediate hosts. In fish, third-stage larvae of the genus Anisakis encapsulates on the surfaces of the visceral organs, mainly in the mesenteries and liver.…”
Section: Akdeniz'de Yakalanan Dülger Balığındakimentioning
confidence: 99%